Foster care in Egypt: A study of policies, laws, and practice. - Ali, Samar Mohamed (AUC Knowledge Fountain, 2015)
Foster care in Egypt is regulated by Ministry of Social Solidarity according to detailed procedures of the child law no 126 for the year 1996 and its amendments of the year 2008. The system combines features of western foster care as well as adoption with the guidelines of Islamic Kafalah system. Children who are deprived from parental care for any reason are eligible to enter the foster care system. This qualitative study analyses the child law against the UN guidelines on alternative care to identify legislative and procedural gaps. It also analyses the current field practices of how placement of children with foster families take place against what is actually mentioned in the child law to identify challenges and opportunities for the enhancement of the service. The study has shown significant discrepancies between practice and national and international legislation.